Moisture variation inferred from tree rings in north central China and its links with the remote oceans - Zeyu Zheng (Nature Portfolio, 2021)
Abstract In this study we presented a composite standard chronology, spanning 1635–2018 to reconstruct May–July moisture variation in north central China. Our reconstruction revealed four severe dry epochs and five pronounced wet epochs. Additionally, spatial correlation analysis of our reconstruction with the actual self-calibrating Palmer drought severity index showed that our reconstruction was representative of large-scale May–July moisture changes. Both the severe dry and pronounced wet epochs showed one-to-one correspondence with other reconstructions nearby during their common periods, which demonstrated the reliability of our reconstruction backwards in time. Spectral analysis showed that significant spectral peaks were found at 2.1–3.8 years, which fell within the overall bandwidth of the El Niño-Southern Oscillations (ENSO). The spatial correlation patterns between our reconstruction and sea surface temperature (SST) in the equatorial eastern Pacific further confirmed the link between regional moisture and ENSO, with warm-phase ENSO resulting in low moisture and vice-versa. However, this link was time-dependent during the past four centuries, and was modulated by different phases of SST in the tropical Indian Ocean. Additionally, significant peaks at 24.9–46.5 years and spatial correlation patterns indicated that the Pacific Decadal Oscillation and the North Atlantic Oscillation may be the possible forcing factors of regional moisture at lower frequencies.